The Relationship between Personality, Sense of Efficacy, and Stress in Korean Teachers - Park, Subin; Song, Yul-Mai; Ko, Guy-Nueo; Jhung, Kyungun; Ha, Kyooseob; Lee, Young-Ryeol; Kim, Yeni (Psychiatry investigation, 2016)
Several studies have linked teachers' personality characteristics and sense of efficacy to stress. However, investigating the relationship between these three constructs in this context was limited. This study aims to investigate the relationship between personality, sense of efficacy and perceived stress among Korean teachers. A total of 137 teachers working in elementary, middle, and high schools located in Seoul, South Korea were recruited for the study. The participants were administered Temperament and Character Inventory, Teacher's Sense of Efficacy Scale (TSES), and Perceived Stress Scale. The TSES was negatively correlated with harm avoidance and positively correlated with persistence, self-directedness, cooperativeness, and self-transcendence. Perceived stress was positively correlated with harm avoidance and negatively correlated with persistence and self-directedness. The path analysis showed that harm avoidance directly predicted perceived stress (β=0.37, 95% CI=0.21-0.53, p=0.002), and self-directedness and persistence predicted one's sense of efficacy (β=0.18, 95% CI=0.01-0.39 and β=0.31, 95% CI=0.10-0.47), which predicted perceived stress (β=-0.21, 95% CI=-0.39 to -0.02). The results of the present study indicate that harm avoidance might be associated with stress-proneness, while persistence, self-directedness, and sense of efficacy might act as protective resources against stress in Korean teachers.